STRATEGI PEMASARAN MELALUI MARKETPLACE DALAM UPAYA PENINGKATAN PENJUALAN PADA UMKM KLASTER OLAHAN PANGAN DI KOTA SEMARANG - Rahmadani Nur Permanawati; Ketut Sudarma; Made Virma Permana; Ascaryan Rafinda (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
The increase in population growth in Indonesia has led to an increase in food consumption. The need for food consumption will always increase, so the processed pangen cluster MSMEs are predicted to continue to grow significantly so that they can meet the necessary food needs. The Cooperative and MSME Agency of Semarang City noted that processed food products still dominate the types of SMEs in Semarang City at 55%. However, these SMEs still market their products in a simple way, where they make products based on what they can do and sell their products without any maximum effort. As a result of such marketing conditions, their businesses are difficult to develop. On the other hand, competition in the business world has become very tight in the current era of globalization. Therefore, this service aims to provide education for residents and managers of food processing cluster MSMEs in Semarang city about the importance of utilizing marketplaces to increase sales for their products. In a broader scope, it can advance the potential development of MSMEs in the processed food sector in the city of Semarang. The output targets of this service are publications in mass media, publications in national service journals, and video highlights of activities.